The Educational Role of Tauh Dance in Kenduri Sko Custom Rituals in Pulau Sangkar Village - Chintia Pratama Putri; Darmansyah Darmansyah (International Journal of Educational Dynamics, 2022)
This study aims to analyze and describe the educational role of the Tauh Dance in the Kenduri Sko traditional ritual, as well as answer why the Tauh Dance is returned to be cultivated in the Pulau Sangkar village community. This research method is descriptive qualitative. The research location is in the village of Pulau Sangkar, and the research informants are indigenous peoples, traditional stakeholders, artists, and related governments. The research instrument was the researcher himself as key instrument, assisted by observation and interview guidelines. Data was collected through interviews, observations, literature studies, and documentation. Data were analyzed using Miles and Huberman's pattern, namely collecting data, reducing data, presenting data, testing data, and concluding the results of data analysis. This study's findings explain that the Tauh Dance has a close relationship with the Kenduri Sko traditional ritual, and the Tauh Dance acts as a means of connecting between the real world and the supernatural world, namely humans and the ancestral spirits of the Sangkar Island community. The Tauh Dance plays a role in providing an overview of the characteristics of the candidate for the governor to be elected in the Kenduri Sko ritual, through the visible expressions of the Dance' movements and expressions. With the reason that the Tauh Dance is a cultural heritage as well as a cultural identity that must be maintained, the Tauh Dance can be returned to its position as a cultural tradition by the people of Pulau Sangkar village.